1988
DOI: 10.1086/185318
|View full text |Cite
|
Sign up to set email alerts
|

An imaging observation of SN 1987A at gamma-ray energies

Abstract: Cl 1m. Tllt Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…The daughter products of radioactive elements are usually not in their nuclear ground states, but rapid de-excitation occurs through the emission of γ-ray lines (Table 6.2). The nuclear decay lines of 56 Co at 847 keV and 1238 keV have been detected from SN 1987A by several balloon and satellite experiments (Cook et al, 1988;Mahoney et al, 1988;Sandie et al, 1988;Teegarden et al, 1989, see also Sect. 9.2).…”
Section: Line Emission Associated With Radioactivitymentioning
confidence: 91%
“…The daughter products of radioactive elements are usually not in their nuclear ground states, but rapid de-excitation occurs through the emission of γ-ray lines (Table 6.2). The nuclear decay lines of 56 Co at 847 keV and 1238 keV have been detected from SN 1987A by several balloon and satellite experiments (Cook et al, 1988;Mahoney et al, 1988;Sandie et al, 1988;Teegarden et al, 1989, see also Sect. 9.2).…”
Section: Line Emission Associated With Radioactivitymentioning
confidence: 91%
“…However, more 56 Co positrons will escape if the expansion is fast (Cassé et al, 2004;Vink, 2004). This led Cassé et al (2004) to the suggestion that a hypernova in the Galactic center region may be responsible for the 511 keV electronpositron line emission from that region (Kinzer et al, 2001; (Cook et al, 1988;Mahoney et al, 1988;Sandie et al, 1988;Teegarden et al, 1989), and the gammaray spectrometer (GRS) on board the Solar Maximum Mission (SMM) satellite (Matz et al, 1988;Leising and Share, 1990, see Fig. 2).…”
Section: Gamma-ray Lines From Supernovaementioning
confidence: 99%
“…Gamma-ray lines from 56 Co decay, at 847 and 1238 keV, were detected in SN 1987A with the GRS instrument of the SMM satellite (Matz et al 1988) and confirmed by several ballon-borne instruments (i.e., Teegarden et al 1989, Mahoney et al 1988, Sandie et al 1988, Cook et al 1988, Rester et al 1989. One surprising fact was the appearence of these lines only 200 days after the explosion (Matz et al, 1988), much earlier than expected.…”
Section: Observational Cluesmentioning
confidence: 71%